miR-130a activates the VEGFR2/STAT3/HIF1α axis to potentiate the vasoregenerative capacity of endothelial colony-forming cells in hypoxia - Jasenka Guduric-Fuchs; Edoardo Pedrini; Judith Lechner; Sarah E.J. Chambers; Christina L. O'Neill; Joana Mendes Lopes de Melo; Varun Pathak; Rachel H. Church; Stuart McKeown; James Bojdo; Kiran J. Mcloughlin; Alan W. Stitt; et al. (Elsevier, 2021)
Hypoxia modulates reparative angiogenesis, which is a tightly regulated pathophysiological process. MicroRNAs (miRNAs) are important regulators of gene expression in hypoxia and angiogenesis. However, we do not yet have a clear understanding of how hypoxia-induced miRNAs fine-tune vasoreparative processes. Here, we identify miR-130a as a mediator of the hypoxic response in human primary endothelial colony-forming cells (ECFCs), a well-characterized subtype of endothelial progenitors. Under hypoxic conditions of 1% O2, miR-130a gain-of-function enhances ECFC pro-angiogenic capacity in vitro and potentiates their vasoreparative properties in vivo. Mechanistically, miR-130a orchestrates upregulation of VEGFR2, activation of STAT3, and accumulation of HIF1α via translational inhibition of Ddx6. These findings unveil a new role for miR-130a in hypoxia, whereby it activates the VEGFR2/STAT3/HIF1α axis to enhance the vasoregenerative capacity of ECFCs.